Microneurorrhaphy of the mentonian nerve during the removal of a giant odontoma - André Lustosa SOUZA; Emerson Filipe de Carvalho NOGUEIRA; Paulo Alexandre da SILVA; Ricardo José de Holanda VASCONCELLOS; Airton Vieira Leite SEGUNDO (Faculdade São Leopoldo Mandic, 2019)
The aim of this article is to describe a surgical technique of option in the treatment of large tumors in jaw whose risk of accidental rupture of the mental nerve presents increased by the report of a patient with mandibular giant case of odontoma. The option for intraoral access, intentional sectioning of the mentonian nerve, followed by resection of the tumor and the installation of fixation material, which in turn was followed by microneurorraphy. A surgical microscope was used to perform microneurorrhaphy of the mentonian nerve with Nylon 8-0 wire. The evolution of the patient was satisfactory, with no complaints or complications. A mechanical assessment for torque and pressure was conducted using wire with a diameter of 1.0mm and 2.5mm, respectively. The sensitivity of the patient's lower lip returned to normal within 120 days of the surgery. Significant enucleations or resections in the mandible involves a great risk of accidental nervous rupture, with permanent sequelae. In these cases, the intentional section of the mentonian nerve, followed by microneurorrhaphy, is a viable option, particularly in young patients. The results of this procedure tend to be more predictable than accidental nervous ruptures.